Immune Response of Amebiasis and Immune Evasion by Entamoeba histolytica - Nakada-Tsukui, Kumiko; Nozaki, Tomoyoshi (Frontiers in Immunology, 2016)
Entamoeba histolytica is a protozoan parasite and the causative agent of amebiasis. It is estimated approximately 1% of humans are infected with E. histolytica, resulting in an estimate of 100,000 deaths annually. Clinical manifestations of amebic infection range widely from asymptomatic to severe symptoms including dysentery and extra-intestinal abscesses. Like other infectious diseases, it is assumed that only ~20% of infected individuals develop symptoms, and genetic factors of both the parasite and humans as well as the environmental factors, e.g., microbiota, determine outcome of infection. There are multiple essential steps in amebic infection: degradation of and invasion into the mucosal layer, adherence to the intestinal epithelium, invasion into the tissues, and dissemination to other organs. While the mechanisms of invasion and destruction of the host tissues by the amoebae during infection have been elucidated at the molecular levels, it remains largely uncharacterized how the parasite survive in the host by evading and attacking host immune system. Recently, the strategies for immune evasion by the parasite have been unraveled, including immunomodulation to suppress IFN-γ production, elimination of immune cells and soluble immune mediators, and metabolic alterations against reactive oxygen and nitrogen species to fend off the attack from immune system. In this review, we summarized the latest knowledge on immune reaction and immune evasion during amebiasis.